The influence of service quality and the application of sharia principles on the smoothness of customer installment payments at PT. Massu Tumbu Abadi - Nasliana; Wardihan Sabar; Ayu Ruqayyah Yunus; Siti Nur Hadyja Taha (www.amertainstitute.com, 2024)
This research aims to analyze the influence of service quality and the application of sharia principles on the smoothness of customer installment payments at PT Massu Tumbu Abadi. The method used in this research is quantitative, the criteria used as a sample are all customers of PT. Massu Tumbu Abadi 2021-2023 and the sample was determined using the Slovin formula with a sample size of 90 respondents. Data collection methods in this research are observation, documentation and questionnaires. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, and multiple linear regression. analysis was carried out using the IMB SPSS-23 analysis tool. The research results show that service quality has a negative and significant effect on the smoothness of installment payments, while the application of sharia principles has a positive and significant effect. Simultaneously, the two independent variables have a significant influence on the smoothness of customers in paying installments. The conclusion of this research is that service quality and the application of sharia principles simultaneously influence the smoothness of customers in making installment payments at PT Massu Tumbu Abadi.